MODELLING AND SIMULATING HYBRID ELECTRICAL VEHICLE FOR TOYOTA SOLUNA WITH PARALLEL DRIVE TRAIN CONFIGURATION - Danny Setiawan; Mohammad Yamin (International Journal Science and Technology, 2022)
This simulation was using the parallel configuration in Simulink modeling (MATLAB software) to be obtained engine and vehicle performance result. The base vehicle using Toyota Soluna with added parallel drive train configuration with electric motor in rear side, the simulation purpose for determined an efficiency using electric motor with a model brushless DC motor maximum power 11 kW. Another purpose was knowing maximum velocity for Toyota Soluna using ICE engine with added a battery and electrical component using simulation, this simulating would be run after connecting subsystems inside program, the subsystem resembled a engine function, electrical component, transmission and mechanical component.